2016
DOI: 10.1016/j.tem.2016.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Role of Sex Steroids in β Cell Function, Growth, and Survival

Abstract: The gonads have long been considered as endocrine glands producing sex steroids such as estrogens, androgens and progesterone, for the sole purpose of sexual differentiation, puberty and reproduction. Reproduction and energy metabolism are tightly linked, however, and gonadal steroids play an important role in sex-specific aspects of energy metabolism in different physiological conditions. In that respect, gonadal steroids also influence the secretion of insulin in a sex-specific manner. This review presents a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
68
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 104 publications
(69 citation statements)
references
References 85 publications
(91 reference statements)
1
68
0
Order By: Relevance
“…Oestrogen directly stimulates insulin secretion by pancreatic β‐cells and improves peripheral insulin sensitivity (Mauvais‐Jarvis et al . ). We did not perform in vivo experiments to investigate the direct effect of oestrogen in insulin secretion in the EW model, which is a limitation of our study.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Oestrogen directly stimulates insulin secretion by pancreatic β‐cells and improves peripheral insulin sensitivity (Mauvais‐Jarvis et al . ). We did not perform in vivo experiments to investigate the direct effect of oestrogen in insulin secretion in the EW model, which is a limitation of our study.…”
Section: Discussionmentioning
confidence: 97%
“…Some studies have addressed the role of sex steroids on pancreatic β‐cells (Nadal et al . ; Mauvais‐Jarvis, ). Oestrogens act on the pancreatic islets by binding to their α‐type receptors, resulting in increased biosynthesis and glucose‐stimulated insulin secretion (Nadal et al .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We reported that testosterone action on AR β-cells amplifies the insulinotropic action of GLP-1 on its receptor via a cAMP-dependent protein kinase-A pathway (Navarro et al, 2016). Thus, androgen deficiency predisposes to T2D via the combination of loss of androgen action in peripheral tissues producing insulin resistance and loss of androgen action in β-cells producing β-cell failure to compensate for insulin resistance (Mauvais-Jarvis, 2016b; Navarro et al, 2015; Navarro et al, 2016). …”
Section: Introductionmentioning
confidence: 99%